Descriptions of eight new Acrogonia species from the Amazon region, including peculiar features of the female genitalia (Hemiptera: Cicadellidae: Cicadellinae: Proconiini) - Silva, Roberta Dos Santos Da; Cavichioli, Rodney R.; Takiya, Daniela M.; Mejdalani, Gabriel (Zootaxa, 2017)
Eight new species of the agriculturally important sharpshooter genus Acrogonia Stål, 1869 are described and illustrated from Brazil (one of them also recorded from Peru): A. amazonensis sp. nov. (state of Amazonas), A. clarae sp. nov. (states of Amazonas and Amapá), A. barbara sp. nov. (state of Mato Grosso), A. youngi sp. nov. (department of Madre de Dios in Peru and state of Acre), A. albertoi sp. nov. (state of Pará), A. tenuis sp. nov. (state of Mato Grosso), A. filiformis sp. nov. (states of Pará and Mato Grosso), and A. interrupta sp. nov. (state of Mato Grosso). In addition to the external morphology, color pattern and male genitalia, this paper includes detailed descriptions and illustrations of the female genitalia of three new species (A. barbara, A. filiformis and A. tenuis). The first ovipositor valvulae of A. tenuis are quite peculiar because they bear a large basal lobe and a projection on the median portion of the ventral margin, both displaying setae. Females of the other five new species are not known.